Ebola Hemorrhagic Fever Associated with Novel Virus Strain, Uganda, 2007–2008 - Wamala, Joseph F.; Lukwago, Luswa; Malimbo, Mugagga; Nguku, Patrick; Yoti, Zabulon; Musenero, Monica; Amone, Jackson; Mbabazi, William; Nanyunja, Miriam; Zaramba, Sam; Opio, Alex; Lutwama, Julius J.; et al. (Emerging infectious diseases, 2010)
During August 2007–February 2008, the novel Bundibugyo ebola virus species was identified during an outbreak of Ebola viral hemorrhagic fever in Bundibugyo district, western Uganda. To characterize the outbreak as a requisite for determining response, we instituted a caseseries investigation. We identified 192 suspected cases, of which 42 (22%) were laboratory positive for the novel species; 74 (38%) were probable, and 77 (40%) were negative. Laboratory confirmation lagged behind outbreak verification by 3 months. Bundibugyo ebola virus was less fatal (case fatality rate 34%) than Ebola viruses that had caused previous outbreaks in the region, and most transmission was associated with handling of dead persons without appropriate protection (adjusted odds ratio 3.83, 95% confidence interval 1.78–8.23). Our study highlights the need for maintaining a high index of suspicion for viral hemorrhagic fevers among healthcare workers, building local capacity for laboratory confirmation of viral hemorrhagic fevers, and institutionalizing standard precautions.
Keywords: Ebola Hemorrhagic fever; Novel Virus Strain